Analisis Wacana pada Editorial Majalah Lentera Edisi Salatiga Kota Merah - Piri, Ilona Estherina Ch.; Warouw, Desie M. D.; Rembang, Max R. (ACTA DIURNA KOMUNIKASI, 2018)
The mass media has a major role in the formation of public opinion. The news of the mass media is often able to change the political views of a person, a group of people, even people within a country. Mass media ideally consists of several rubrics. Rubric (column) is a room on the pages of newspapers, magazines, or other print media about an aspect or activity. One of the most common rubrics in the mass media is â€˜editorialâ€™. Editorial rubric is an article in a newspaper that reveal the owner’s perspective about the main subject that is usually present in a media. Lentera Magazine is a journalistic product of a Student Press from Social Science and Communication Faculty, Satya Wacana Christian University (UKSW). On October 9th 2015, LPM Lentera published a magazine entitled "Salatiga Kota Merah". The magazine caused controversy for citizen of Salatiga which later became a national issue. The main issue of the magazine that cause controversy is story about G30S in Salatiga. This Research use discourse analysis theory of Teun Van Dijk, which examines three dimensions of discourse, text, social cognition, and social context. This research collects data with documentation techniques and literature studies. In the text dimension, the editorial column of â€˜Salatiga Kota Merahâ€™ takes general theme about perspective of editorial staff of G30S issue in Salatiga. In social context side, negative stigma about PKI and other things related to communism have been built in Indonesian society since the orde baru era. This is provoked public controversy when Lentera wrote about G30S in Salatiga. Keyword: Mass Media, Lentera Magazine, Discourse Analysis, Teun Van Dijk